ANALISIS KEMAMPUAN PUBLIC SPEAKING DAN KOMUNIKASI KONVERGENSI HOST PADA ACARA TALK SHOW MATA NAJWA METRO TV - Yeni Setyowati; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
The study aims to describe and understand the public assessment of public speaking skills and conversgence of the host on The Mata Najwa talk show. The methods of research used is quantitative and qualitative combination (mixed method) methods with an approach to case studies. The theory used to support this study was the rhetorical theory of Aristotle and the accommodation theory of communication. The results of this study were found that public speaking and convergence communication of Najwa Shihab overall was good. Everyone has the characteristics, tastes and also educational factors that can influence the public judgment on the poverty of Najwa Shihab. The suggestion Najwa should still retain its trademark as a host with a sharp, bold, and firm style, while paying attention to communication ethics.